2015
DOI: 10.15623/ijret.2015.0403001
|View full text |Cite
|
Sign up to set email alerts
|

Standard Water Quality Requirements and Management Strategies for Fish Farming (A Case Study of Otamiri River)

Abstract: A study on standard water quality requirements and management strategies suitable for fish farming is presented. The water quality criteria studied based on physical, chemical and biological properties of water include temperature, turbidity, total suspended solids (TSS), total dissolved solid (TDS), nitrate-nitrogen, pH, biochemical oxygen demand (BOD) and total hardness. Water samples from Otamiri River in Imo state, Nigeria, were analyzed based on the afore-mentioned criteria to assess its suitability as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…BOD is a measure of the quantity of oxygen used by microorganisms (aerobic bacteria) in the oxidation of organic matter. A sample with BOD between 1.0 and 2.0 mg/L indicates clean water, BOD of 3.0 to 5.0 mg/L indicates a moderately clean water and if the value is more significant than 5 mg/L, indicates a polluted water source, which means the water should be treated before been put Open Access Library Journal to used [34]. The result obtained showed that the BOD values ranged between 4.0 to 6.0 mg/L for fish wastewater while those of the borehole and river water sources 3.0 -3.7 mg/L respectively.…”
Section: Biological Oxygen Demand (Bod)mentioning
confidence: 99%
“…BOD is a measure of the quantity of oxygen used by microorganisms (aerobic bacteria) in the oxidation of organic matter. A sample with BOD between 1.0 and 2.0 mg/L indicates clean water, BOD of 3.0 to 5.0 mg/L indicates a moderately clean water and if the value is more significant than 5 mg/L, indicates a polluted water source, which means the water should be treated before been put Open Access Library Journal to used [34]. The result obtained showed that the BOD values ranged between 4.0 to 6.0 mg/L for fish wastewater while those of the borehole and river water sources 3.0 -3.7 mg/L respectively.…”
Section: Biological Oxygen Demand (Bod)mentioning
confidence: 99%